The Integration of Aswaja Education Values through the Study of the Book of Treats of the Ahlusunnah Wal Jama'ah on Lailatul Ijtima Tradition - Farih, Khairul; Jaenullah, Jaenullah; Muslimin, Ahmad (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to analyze the role of the Ahlusunnah Wal Jamaah Treatise in reinforcing the values of Ahlusunnah wal Jamaah (Aswaja) within the tradition of Lailatul Ijtima, as practiced by the Sukabumi Branch Representative Council of Nahdlatul Ulama in Bandar Lampung City. Lailatul Ijtima is a routine tradition held by Nahdlatul Ulama (NU) that serves to strengthen fellowship among members, deepen religious knowledge, and reaffirm a commitment to moderate Islamic teachings rooted in the Aswaja perspective. As the primary reference in this tradition, the Ahlusunnah Wal Jamaah Treatise plays a vital role in guiding participants toward sound Islamic creed (aqidah), sharia aligned with the Sunnah, and virtuous character (akhlaq). This study employs a qualitative research approach, utilizing observation, interviews, and documentation to examine the implementation of Lailatul Ijtima at the Sukabumi NU Branch. Data were collected through interviews with religious leaders, administrators, and participants to assess the impact of the Treatise on enhancing understanding and practice of Aswaja values among NU members. The findings reveal that the Ahlusunnah Wal Jamaah Treatise significantly contributes to deepening the understanding and application of Aswaja teachings, particularly within the Lailatul Ijtima tradition. The text emphasizes the principles of moderate belief, sharia consistent with the Qur'an and Hadith, and the importance of moral integrity and interfaith tolerance. Additionally, the Treatise serves as a unifying reference that fosters collective awareness, preserves religious traditions, and guards against deviant ideologies. This research contributes to the growing body of literature on contextual Aswaja practice at the grassroots level, particularly within regional NU communities. It offers practical insights into how classical Islamic texts are utilized in religious traditions to strengthen a moderate Islamic identity. The findings may also inform educational institutions and religious organizations in developing contextual and tradition-based Islamic learning strategies that remain relevant in contemporary society